2017
DOI: 10.1098/rstb.2016.0234
|View full text |Cite
|
Sign up to set email alerts
|

Boldness traits, not dominance, predict exploratory flight range and homing behaviour in homing pigeons

Abstract: Group living has been proposed to yield benefits that enhance fitness above the level that would be achieved through living as solitary individuals. Dominance hierarchies occur commonly in these social assemblages, and result, by definition, in resources not being evenly distributed between group members. Determinants of rank within a dominance hierarchy can be associated with morphological characteristics, previous experience of the individual, or personality traits such as exploration tendencies. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
0
25
2
Order By: Relevance
“…For example, our results suggested that bold pigeons are, on average, faster individual fliers, so leaders among birds may be better at escaping from predators than followers. In fact, a recent study has shown that bold pigeons who demonstrated a lack of neophobia tend to develop more efficient routes and thus fly home faster during solo homing flights than shy birds who are neophobic [40]. Secondly, raptor attack strategies may be different from those used by aquatic predators.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our results suggested that bold pigeons are, on average, faster individual fliers, so leaders among birds may be better at escaping from predators than followers. In fact, a recent study has shown that bold pigeons who demonstrated a lack of neophobia tend to develop more efficient routes and thus fly home faster during solo homing flights than shy birds who are neophobic [40]. Secondly, raptor attack strategies may be different from those used by aquatic predators.…”
Section: Discussionmentioning
confidence: 99%
“…Homing pigeons (N = 18), all aged 1-1.5 years, were used in the experiments. They were housed in two separate groups of nine, in purpose-built lofts (7 x 6 ft) at Royal Holloway, University of London, U.K. (see Portugal, Ricketts, et al, 2017;Portugal, Sivess, et al, 2017 for further husbandry details). Food (Johnstone & Jeff Four Season Pigeon Corn, Gilberdyke, U.K.), water and grit (Versele-Laga-Colombine Grit and Redstone, Deinze, Belgium) were provided ad libitum.…”
Section: Methods Subjects and Morphological Measurementsmentioning
confidence: 99%
“…Our first goal was to establish a new method of tracking visually guided behavior in pigeons in the field through simultaneous recordings of head movements using an inertial measurement unit (IMU) and flight trajectories using global positioning system (GPS) during homing flights. Although lightweight GPS devices have become well established as a reliable technology for tracking moment-tomoment changes in the flight trajectories of pigeons (Biro et al, 2004;Dennis et al, 2007;Gagliardo et al, 2011;Guilford et al, 2004;Lipp et al, 2004;Martinho et al, 2015;Portugal et al, 2017;Schiffner and Wiltschko, 2009), the use of an IMU to track head movement has never been attempted in the field. IMUs are equipped with an accelerometer, a gyroscope and a magnetometer, and hence can provide highly accurate reconstructions of motion and turns; they can also provide an estimate of absolute orientation with respect to gravity and the Earth's magnetic field (e.g.…”
Section: Introductionmentioning
confidence: 99%